Global citizenship elements in Malaysian Primary School Curriculum towards Sustainable Development Goals (SDGS) - Syed Zakaria, Sharifah Zarina; Raja Abu Bakar, Raja Nur Amirah; Mat Isa, Nasharudin; Mahmud, Siti Nur Diyana; Abdullah, Azlina; Che Ahmad, Che Nidzam; Syed Abdullah, Sharifah Intan Sharina; Abd. Majid, Nuriah; Razman, Muhammad Rizal (EM International, 2021)
Global Citizenship (GC) is still a new concept in Malaysian education scenario, and existing research shows that a critical approach to teaching and learning about global issues is largely absent within Malaysian school settings. Thus, the purpose of this study is to explore the GC elements, embedded in the Malaysian education curriculum within the UNESCO framework. This paper will discuss the result of document analysis done on Malaysian primary school core subjects, which used critical discourse analysis to analyze the relevant parts of the curriculum within the core subjects. The analysis revealed that GC is taught across the curriculum in Malaysia, which aims to increase students’ knowledge, skills and behavior towards sustainability. GCE was presented in the curriculum as a multidisciplinary topic which follows through the values, aims and tasks of the core subjects. This study provides a clear starting point for future research of GC and its implementation and impacts in Malaysian education system, and hope to open the eyes and minds of the policy makers in Malaysia, the importance of GC which has a crucial role to play in tackling injustices and making the world a more just and sustainable place.